The Study of Selection Bottle Packaging for Carbonated Beverages - Susanti, Ari Diana; Jalesaputri, Diaz Dzulriyana; Hasanah, Fadhilah Rahmatul; Romadhoni, Achmad Tegar; Gultom, Alvin Petrus (Equilibrium Journal of Chemical Engineering, 2022)
ABSTRACT. The growth of the packaged beverages market in Indonesia is overgrowing. One sector of packaged beverages is carbonated beverages and bottled water. The main problem with packaged beverages containing dissolved gases is maintaining product quality during shelf life. Packaging materials and packaging lids cause a decrease in dissolved gas levels in beverages. Therefore, this study aims to analyze leaks in polyethylene terephthalate and glass bottles so that can use them to estimate the shelf life of the product. This study uses water, 3 types of glass bottles, and 1 type of plastic bottle. Bottles filled with water with various filling volumes of 40%v/v, 60%v/v, and 80%v/v were then analyzed for bottle leakage for 8 days. The results showed that effectively used a glass bottle with a volume of 250mL filled with more than 80%v/v, this was because it had the least leakage rate compared to others. In addition, this bottle has an attractive visual, easy labeling, and the size is not too large (ergonomic).Keywords: Glass bottle, plastic bottle, leakage test, shelf life